OP0195 VASCULARIZED THREE-DIMENSIONAL MODELS OF HUMAN SKIN FIBROSIS. (2nd June 2020) - Matei, A. E.; Chen, C. W.; Kiesewetter, L.; Györfi, A. H.; LI, Y. N.; Trinh-Minh, T.; Van Kuppevelt, T.; Hansmann, J.; Juengel, A.; Schett, G.; Groeber-Becker, F.; Distler, J.
Abstract : Background: The complex pathophysiological processes that result in fibrotic tissue remodeling in systemic sclerosis involve interplay between multiple cell types (1). Experimental models of fibrosis are essential to provide a conceptual understanding of the pathogenesis of these diseases and to test antifibrotic drugs. Current models of fibrosis have important limitations: the in vivo models rely on species that are phylogenetically distant, whereas the in vitro models are oversimplified cultures of a single cell type in an artificial two-dimensional environment of excessive stiffness, which imposes an unphysiological cell polarization (2). Objectives: Here we evaluated the potential use of vascularized, three-dimensional in vitro human skin equivalents as a novel model of skin fibrosis and a platform for the evaluation of antifibrotic drugs. Methods: Skin equivalents were generated by seeding human endothelial cells, fibroblasts and keratinocytes on a decellularized porcine extracellular matrix with perfusable vascular structure. The skin models were cultured for one month in a system that ensured perfusion of the vascular network at physiological pressure. Fibrotic transformation induced by TGFβ and response to nintedanib as an established antifibrotic drug was evaluated by capillary Western immunoassays, qPCR, histology and immunostaining. Results: The vascularized human skin equivalents formed the major skin structures relevant for the pathogenesis of fibrosis: a polarized, fully matured epidermis, a stratified dermis and a perfused vessel system with small capillaries. Exposure to TGFβ led to the fibrotic transformation of the skin equivalents, with activated TGFβ downstream pathways, increased fibroblast-to-myofibroblast transition and excessive deposition of extracellular matrix. Treatment of models exposed to TGFβ with nintedanib (a drug with proven antifibrotic effects) ameliorated the fibrotic transformation of skin equivalents with reduced TGFβ signaling, fibroblast-to-myofibroblast transition and decreased extracellular matrix deposition. Conclusion: Here we describe a novel in vitro model of skin fibrosis. Our data show that vascularized skin equivalents can reproduce all skin layers affected by fibrosis, that, upon exposure to TGFβ, these models recapitulate key features of fibrotic skin and that these skin models can be used as a platform for evaluation of antifibrotic drugs in a setting with high relevance for human disease. References: [1]Distler JHW, Gyorfi AH, Ramanujam M, Whitfield ML, Konigshoff M, Lafyatis R. Shared and distinct mechanisms of fibrosis. Nature reviews Rheumatology. 2019;15(12):705-30. [2]Garrett SM, Baker Frost D, Feghali-Bostwick C. The mighty fibroblast and its utility in scleroderma research. Journal of scleroderma and related disorders. 2017;2(2):69-134. Disclosure of Interests: Alexandru-Emil Matei: None declared, Chih-Wei Chen: None declared, Lisa Kiesewetter: None declared, Andrea-Hermina Györfi: None declared, Yi-Nan Li: None declared, Thuong Trinh-Minh: None declared, Toin van Kuppevelt: None declared, Jan Hansmann: None declared, Astrid Juengel: None declared, Georg Schett Speakers bureau: AbbVie, BMS, Celgene, Janssen, Eli Lilly, Novartis, Roche and UCB, Florian Groeber-Becker: None declared, Jörg Distler Grant/research support from: Boehringer Ingelheim, Consultant of: Boehringer Ingelheim, Paid instructor for: Boehringer Ingelheim, Speakers bureau: Boehringer Ingelheim